Pengaruh Kualitas Produk, Persepsi Harga, dan Promosi terhadap Keputusan Pembelian untuk Meningkatkan Potensi Pembelian Kembali Pelanggan di Yummy Kitchen Setiabudi Jakarta Selatan - Dwi Mayasari; Surono Surono (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2023)
This study aims to determine and analyze the effect of product quality, price perception, and promotion on purchasing decisions to increase the potential for customer repurchase at Yummy Kitchen Setiabudi, South Jakarta. The population in this study were all customers of Yummy Kitchen Setiabudi, South Jakarta. This research method is quantitative research. The sample in this study amounted to 100 respondents. Purposive sampling was used in sampling. Respondents who had visited at least twice were included in the purposive sampling group. Data analysis uses Structural Equation Modeling with the help of SmartPLS software. The results of the study show that product quality, price perceptions, promotions have an effect on purchasing decisions. Purchase decisions affect customer repurchase at Yummy Kitchen Setiabudi, South Jakarta. The test results show an NFI value of 0.748 so that the research model is 74.8% fit.